Pathogenesis of Non-Hodgkin's Lymphoma - Nogai, Hendrik; Dörken, Bernd; Lenz, Georg (Journal of clinical oncology, 2011)
The understanding of the molecular pathogenesis of non-Hodgkin's lymphomas (NHL) has significantly improved in recent years. Advances in molecular biology and genetics lead to the identification and characterization of several oncogenic pathways involved in lymphomagenesis. This knowledge will ultimately lead to improved diagnostic and therapeutic strategies for patients with NHL. This review summarizes current concepts of the molecular pathogenesis of the most common NHL subtypes, with a special emphasis on diffuse large B-cell lymphoma, the most common lymphoma subtype.